Effects of Hydrogen Peroxide Concentration on Properties of Black Silicon Fabricated by Two-Step Silver-Assisted Wet Chemical Etching for Photovoltaics - Abdulkadir, Auwal; Pakhuruddin, Mohd Zamir (Iraqi Journal of Physics, 2022)
Crystalline silicon (c-Si) has low optical absorption due to its high surface reflection of incident light. Nanotexturing of c-Si which produces black silicon (b-Si) offers a promising solution. In this work, effect of H2O2 concentrations towards surface morphological and optical properties of b-Si fabricated by two-step silver-assisted wet chemical etching (Ag-based two-step MACE) for potential photovoltaic (PV) applications is presented. The method involves a 30 s deposition of silver nanoparticles (Ag NPs) in an aqueous solution of AgNO3:HF (5:6) and an optimized etching in HF:H2O2:DI H2O solution under 0.62 M, 1.85 M, 2.47 M, and 3.7 M concentrations of H2O2 at 5 M HF. On the b-Si, nanowires with 250-950 nm heights and an average diameter of 150-280 nm are obtained. Low concentrations of H2O2 result in denser nanowires with an average length of 900-950 nm and diameters of about 150-190 nm. The b-Si exhibit outstanding broadband antireflection due to the refractive index grading effect represented as WAR within the 300-1100 nm wavelength region. B-Si obtained after etching in a solution with 0.62 M concentration of H2O2, demonstrate WAR of 7.5%. WAR of 7.5% results in an absorption of up to 95.5 % at a wavelength of 600 nm. The enhanced broadband light absorption yields maximum potential short-circuit current density (Jsc(max)) of up to 38.2 mA/cm2, or 45.2% enhancement compared to the planar c-Si reference.